(untitled) (Proceedings of International Educators Conference, 2024)
Enlightener scholar and statesman Abdurauf Fitrat wrote in his “Rahbari najot”: “Our country was famous as the source of enlightenment, rising of culture sun in its time”. Our state was well-known to the world thanks to thousands of popular scholars. Schools and madrassahs which educated hundreds of scientists were called as “cradle of world development” by Abdurauf Fitrat.